The Influence of Corporate Governance, Investment Opportunity Set, and Company Growth on Company Value - Apryany, Andiny; Dalimunthe, Ibram Pinondang (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
Indonesia's economic progress, as reflected in the growth of the capital market, has triggered fierce competition among companies to increase their value in an effort to maximize investor welfare. This study aims to analyze and prove the effect of corporate governance (ACGS), investment opportunity set (MVBVA), and company growth (Growth Asset) on company value (PBV). This study explains the factors that influence company value in the non-cyclical consumer sector and can be used as a reference for management and investors in making strategic decisions to increase company value. The research population consists of non-cyclical consumer companies listed on the Indonesia Stock Exchange from 2019 to 2023. The research sample was determined using purposive sampling with specific criteria, resulting in 69 companies that met the requirements for the research sample. The results show that corporate governance does not affect company value, while investment opportunity set and company growth do affect company value.